Perancangan Buku Ilustrasi ‘Belajar Jajanan Tradisional’ Sebagai Media Edukasi Berbasis Kearifan Lokal Bagi Siswa SDN 1 Tanggungharjo - Panca Ardhi Noer Cahaya; Irdha Yunianto; Ayyub Hamdanu Budi Nurmana M. S (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
Local wisdom, particularly traditional snacks, constitutes an essential part of national cultural identity that needs to be introduced from an early age. However, observations at SDN 1 Tanggungharjo revealed that students' understanding of traditional snacks remains low, compounded by a lack of contextual and engaging visual learning media. This study aims to design an illustrated book titled "Belajar Jajanan Tradisional" (Learning Traditional Snacks) as a local wisdom-based educational medium for grades 3–6 students at SDN 1 Tanggungharjo. The Design Thinking method was employed through five stages: Empathize, Define, Ideate, Prototype, and Test. Data were collected through direct observation, teacher interviews, and student questionnaires. The outcome is a 20-page digital illustrated book in A5 PDF format covering four traditional snacks — klepon, dadar gulung, apem, and kue lapis — with content encompassing their origins, philosophy, cultural values, ingredients, and preparation processes. The applied design elements include character personification, vector cartoon style, bright color palettes based on the snacks' natural colors, rounded sans-serif typography, and a charactercentered layout tailored to the cognitive characteristics of students aged 9–12 years. Trial results demonstrated that the illustrated book effectively enhanced students' understanding of and interest in traditional snacks, while receiving positive feedback from teachers as a contextual and meaningful supplementary medium for thematic learning.